2011
DOI: 10.1161/hypertensionaha.110.157032
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Delivery of Pitavastatin Into Lungs Ameliorates the Development and Induces Regression of Monocrotaline-Induced Pulmonary Artery Hypertension

Abstract: Abstract-Pulmonary artery hypertension (PAH) is an intractable disease of the small PAs in which multiple pathogenic factors are involved. Statins are known to mitigate endothelial injury and inhibit vascular remodeling and inflammation, all of which play crucial roles in the pathogenesis of PAH. We tested the hypothesis that nanoparticle (NP)-mediated delivery of pitavastatin into the lungs can be a novel therapeutic approach for the treatment of PAH. Among the marketed statins, pitavastatin was found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 24 publications
(47 reference statements)
1
71
0
1
Order By: Relevance
“…At least 30 studies have reported beneficial effects from this drug class in a range of animal models (Chen et al, 2011;Dai & Wu, 2011;DeMarco & Habibi, 2009;Gao, Zhu, Shi, & Jing, 2010;RE Girgis, Li, Zhan, & Garcia, 2003;R. E. Girgis et al, 2007;Guerard et al, 2006;Hsu et al, 2009;Ikeda, Nakamura, Akagi, & Kusano, 2010;Kuang, Wang, Pang, Huang, & Burg, 2010;Laudi et al, 2007;M.…”
Section: Statinsmentioning
confidence: 99%
“…At least 30 studies have reported beneficial effects from this drug class in a range of animal models (Chen et al, 2011;Dai & Wu, 2011;DeMarco & Habibi, 2009;Gao, Zhu, Shi, & Jing, 2010;RE Girgis, Li, Zhan, & Garcia, 2003;R. E. Girgis et al, 2007;Guerard et al, 2006;Hsu et al, 2009;Ikeda, Nakamura, Akagi, & Kusano, 2010;Kuang, Wang, Pang, Huang, & Burg, 2010;Laudi et al, 2007;M.…”
Section: Statinsmentioning
confidence: 99%
“…[14][15][16][17] We recently reported that nanoparticle-mediated delivery of pitavastatin showed significant therapeutic effects on pulmonary arterial hypertension, 18) restenosis, 19) ischemia-reperfusion injury, 20) and atherosclerosis 21) in animals by inhibiting the MCP1-CCR2 pathway. Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies.…”
Section: Editorial P472mentioning
confidence: 99%
“…Because PLGA nanoparticles are delivered selectively to inflammatory cells (mainly monocytes) after intravenous administration, 21,22) it is suggested that monocyte-mediated inflammation plays an important role in the mechanism by which pitavastatin-NP exerted beneficial effects in these previous studies. [18][19][20][21] Therefore, in the present study, we used a mouse model of post-infarct LV remodeling and tested the hypothesis that 1) PLGA nanoparticles are selectively delivered to inflammatory cells (mainly activated monocytes) and 2) the nanoparticlemediated targeting of pitavastatin to these inflammatory cells after establishment of MI protects the heart from LV remodeling by inhibiting recruitment of inflammatory monocytes to the infarcted heart.…”
Section: Editorial P472mentioning
confidence: 99%
“…The advantages of NP-mediated drug-delivery systems for the treatment of lung diseases, including PAH, have also been confirmed in other studies. 40,41 According to our prior experiment, the in vitro release profile of EP-NPs showed sustained release of 85% EP for at least 168 hours, with a small burst release. In the current in vivo experiments, fluorescence was faint 7 days after FITC-NP administration (Figure 2).…”
mentioning
confidence: 91%
“…This agrees with a previous study, in which a lactide/glycolide copolymer (PLGA) used as a carrier for intratracheal instillation for 21 days resulted in no toxicologic reactions. 41 Nonetheless, the long-term safety and therapeutic effects of an NP-mediated EP system in PAH should be explored in further studies. In addition, the accumulation or clearance rate of polymeric materials from the lungs over time should be taken into account in providing more information about the use of such a system.…”
mentioning
confidence: 99%